Por uma pedagogia de (multi)letramentos: desafios e possibilidades no contexto do ensino fundamental público em língua portuguesa - Silva, Jeniffer Streb da (2021)
In this research, we analyzed the (multi)literacies practices of 9th grade students in order to verify the uses of reading and text production in a public-school context. For this, (i) we described the events and practices of (multi)literacies in which students participate in their daily lives and in the school context, in order to analyze the interrelation between these two spheres; (ii) we identified the discourses about texts and genres of texts in this context of investigation; and (iii) we propose actions for the development of a (multi)literacy project for the investigated context. The theoretical-methodological contribution used was Critical Genre Analysis (MOTTA-ROTH, 2008) and its founding theories: Sociorethoric (MILLER, 1984; BAZERMAN, 2006; 2009; SWALES, 1990), Critical Discourse Analysis (FAIRCLOUGH, 1992; 2001) and Systemic-Functional Linguistics (HALLIDAY; MATTHIESSEN, 2004, 2014). In addition, we rely on literacy studies, especially in the Pedagogy of (Multi)literacies (KALANTZIS et al., 2016; KALANTZIS; COPE; PINHEIRO; 2020). The corpus of this study was composed of data generated from interviews with students via Google Meet. The results of our analysis indicate that the events and (multi)literacies practices of these students' daily lives occur in a multimodal manner and from different supports, especially those of a digital nature. In relation to the events and practices of the school context, we understood that these are mediated by texts whose preferential language is writing. Interrelating these two contexts, we noted that there is little dialogue between them. In addition, we noted that reading and textual production practices in the school context demonstrate a traditional perception of these processes, since the students' discourses reveal an understanding of text as long, complex, written language. Finally, we understand that our investigation makes it possible to explore the “Experiencing” Knowledge Process, since we know what they read and produce, as well as what they would like to read and produce within the school.